„Na rozdrożu myśli”: białoruski spór o historię w okresie pieriestrojki - Gordziejew, Jerzy (1967– ) (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
The purpose of this article is to provide an overview of the Belarusian historical debate surrounding the ‘blank spots’ in history and the instrumental use of historical narratives during the perestroika era. This debate emerged in the second half of the 1980s in Belarus as a response to the discrepancies between the rigid, state-directed interpretation of history and the unofficial collective memory. It also stemmed from a desire to introduce unexplored topics and previously suppressed aspects of the past into public discourse.
p. 205-229
Summary in English and Russian.
Keywords: perestroika; Belarus 20th c.; ‘blank spots’ of history; Belarus - historiography; Belarus - politics and government - 1991-; perestroyka - Belarus